Perceived usability of chatbots on customer service in organizations: a review of the literature - Casazola Cruz, Oswaldo Daniel (2021)
A chatbot is a software application based on artificial intelligence, which allows to simulate a conversation with a person. However, despite the many benefits, a considerable number of chatbots struggle to satisfy users. The objective of this article was to describe the perceived usability of chatbots in customer service in different organizations. Therefore, the current study performed a systematic review of the literature on Google Scholar and EBSCO data, between the period 2015 and 2020, to analyze the existing evidence regarding (a) the nature of chatbots, (b) its implementation, (c) perceived usability, and (d) the rise of this technology.